In Whose Name : The Islamic World After 9/11 - Abbas (London Thames & Hudson, 2009)
In over 170 duotone images, this title exposes an inside view of a world seen by very few people in the West. Focusing on the resurgence of Islam everywhere on the planet since September 2001, it includes pictures that swell with the undercurrents of global disturbance, uncertainty and threat.
Include Illustrations.
The Islamic World After 9/11.
Keywords: Manners and customs -- Travel -- Islamic countries